AN ANALYSIS OF GRAMMATICAL ERRORS IN ANNOUNCEMENT TEXTS WRITTEN BY THE TENTH GRADE STUDENTS - Nur Aida Arifah; Nanang Bagus Subekti (JELLT (Journal of English Language and Language Teaching), 2020)
English is one of the foreign languages learned by Indonesian students. In the process of learning language, the errors might be made by learners. The complexity of English and its difference from Bahasa Indonesia can lead to students’ errors. This study explored (a) the types of errors found in announcement text written by the tenth-grade students, (b) the type of error which is more frequently committed by the tenth-grade students, and (c) the sources of errors found in announcement texts written by the tenth-grade students. To identify the errors, Surface Strategy Taxonomy was used in this research. Furthermore, interlingual and intralingual errors were identified as the source of errors found. To conduct the study, the researcher applied qualitative research, which case study was the specific type of this study. The data in this study were the announcement texts written by the tenth-grade students. There were five steps in conducting this study, namely; collecting samples of language learners, identification of errors, description of errors, explanation of errors, and error evaluation. The result of this study showed there were 31.82% omission error, 11.36% addition error, 27.27% misformation error, and 29.55% misordering error based on Surface Strategy Taxonomy. Thus, omission error was the highest. Furthermore, there were 34.09% interlingual as the source of errors found, and 65.91% intralingual as the source of errors found. Thus, this study suggests that the English environment is created as possible to minimize the errors of the leaners. Additionally, learners must also be aware of their learning.